2017
DOI: 10.1007/s00268-016-3799-0
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Outcomes Between Single‐Site Robotic and Multi‐port Laparoscopic Cholecystectomy: An Experience from a Tertiary Care Center

Abstract: Multi-port laparoscopic cholecystectomy should remain the gold standard therapy for gallbladder disease. Single-site robotic cholecystectomy is an effective alternative procedure for uncomplicated benign gallbladder disease in properly selected patients. This must be carefully balanced against a high rate of surgical site infection and incisional hernia, and patients should be informed of these risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 45 publications
4
18
0
2
Order By: Relevance
“…The literature search identified thirteen studies with a total of 1411 patients [170182]. Two studies were randomized controlled trials [170, 171] (n = 136 and n = 60), and three were non-randomized comparative studies [172174] (n = 790). The two RCTs and a large non-randomized study (n = 678) compared SIRC with multi-port laparoscopic cholecystectomy (MPLC).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified thirteen studies with a total of 1411 patients [170182]. Two studies were randomized controlled trials [170, 171] (n = 136 and n = 60), and three were non-randomized comparative studies [172174] (n = 790). The two RCTs and a large non-randomized study (n = 678) compared SIRC with multi-port laparoscopic cholecystectomy (MPLC).…”
Section: Resultsmentioning
confidence: 99%
“…Robotic cholecystectomy (Table 1) [1][2][3][4][5][6][7][8][9][10][11][12][13] With the current platform available, two major approaches are used: single site and multi-port. We reviewed the current literature and found 2,039 cases listed in the time frame we choose.…”
Section: Resultsmentioning
confidence: 99%
“…1 When used for benign disease, chronic cholecystitis, or biliary dyskinesia, it has been proven to be an acceptable alternative to traditional cholecystectomy in terms of outcomes, although it is more expensive. 2 When compared to single site laparoscopy, the robotic system developed with the Da Vinci Si/Xi© platform gives the surgen or a surgen a huge advantage of wristed instruments with controlled torque. This might be associated with less postoperative discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…In several trials comparing single‐incision port with multiple‐port procedures, researchers have demonstrated that single‐incision port procedures result in longer operative times, in part because of lack of triangulation. Despite this, a difference in complication rates between single‐incision–port and multiple‐port procedures has not been shown in most human studies, although, in one retrospective study, a higher infection rate was observed in cholecystectomy patients undergoing a single‐incision–port robotic procedure than in patients undergoing a multiple‐port procedure . In a study of 98 dogs undergoing laparoscopic gastropexies and/or ovariectomies, single‐incision–port procedures were found to have significantly shorter operative times compared with multiple‐port procedures; however, there was no difference in complication rates …”
Section: Discussionmentioning
confidence: 99%